Per una rinascita spirituale dell’uomo. Karl Jaspers, la svolta assiale e il progetto della Weltphilosophie - Pacilè, Maria Teresa (Filosofia Morale/Moral Philosophy, 2024)
For a spiritual rebirth of man. Karl Jaspers, the Axial Age and the project of the Weltphilosophie This paper aims to explore Jaspersian notion of “axial revolution”, interpreted as a fundamental turning point in universal human history. In the light of the current debate on the Axial Age and the critical interpretations offered by the comparative sociology (Eisenstadt) and the contemporary historiography (Assman and Bellah), it may be interesting to read the Jaspers’ thesis of axiality as constant spiritual rebirth within the project of a history of world philosophy (Weltphilosophie).